Validation of anthropometric equations for predicting body mass and height in older women - Gilberto Moreira Santos Júnior; Amandio Aristides Rihan Geraldes; Dante Wanderley Lima de Oliveira; Piettra Moura Galvão Pereira; Rodrigo B. de Albuquerque (Universidade Federal de Santa Catarina, 2021)
To investigate the cross-validity of two equations widely used in national research to predict body mass and height in older Brazilians. Additionally, the importance of possible differences between observed and predicted BMI will be investigated with the help of equations. BM and HEI were measured using mechanical scales and portable stadiometers in a sample of 200 older women (66.6 ± 5.43 years) living in Maceió / AL - Brazil. To verify the validity of equations, the following variables were used: Student's t-test, constant error (CE), total error (TE) and standard error of estimation (SEE). To verify agreement between actual and predicted values, the Bland-Altman test was used. The comparison between BM and HEI values obtained through equations and those verified in measurements showed statistically significant differences (p <0.05). CE between predicted and measured values, TE of tested equations, as well as SEE for the prediction of variables: BM (1.66; 0.11 and 6.33), HEI (-0.02; 0.02 and 0.10) and BMI (1.47; 0.10 and 3.24) allowed determining relative values ​​very close to actual ones (2.6%, 1.31% and 5.3% for BM, HEI and BMI respectively); however, values were not statistically significant. The equations analyzed should not be used in a general way for the population of older Brazilian women with characteristics similar to those analyzed in this study. Therefore, further studies should be carried out with the objective of constructing specific equations for the population of older women and hospitalized patients, especially the most fragile ones.